Differentiated tactics of antiepileptic therapy in children with resistant focal epilepsies - Harut N. Aren (Academic Journal of Clinicians, 2024)
Focal epilepsies, also known as partial epilepsies, are characterized by seizures that originate in a specific area of the brain. Resistant focal epilepsies refer to cases where seizures persist despite treatment with appropriate antiepileptic drugs (AEDs). Differentiated tactics of antiepileptic therapy aim to improve seizure control and quality of life in children with resistant focal epilepsies. These tactics involve several key considerations: Comprehensive evaluation: A thorough assessment is essential to identify the precise seizure focus and underlying etiology. This may involve neuroimaging, electroencephalography (EEG), and other diagnostic tests to guide treatment decisions. Multidisciplinary approach: Collaborative care involving epileptologists, neurologists, neuropsychologists, and other specialists can help tailor treatment plans to the specific needs of each child. This may include addressing comorbidities, cognitive and developmental challenges, and psychosocial factors. Individualized medication selection: A careful review of the child’s medication history and response is necessary. The choice of AEDs should consider the seizure type, potential side effects, drug interactions, and the child’s age, comorbidities, and preferences. Polytherapy and combination approaches: In some cases, combining multiple AEDs may be necessary to achieve better seizure control. However, the benefits and risks of polytherapy should be carefully weighed, taking into account potential drug interactions and side effects. Non-pharmacological interventions: Adjunctive therapies, such as ketogenic diet, vagus nerve stimulation, or epilepsy surgery, may be considered if seizures remain uncontrolled despite optimal medication regimens. Regular monitoring, dose adjustments, and close communication between the healthcare team and the child’s caregivers are crucial in managing resistant focal epilepsies. The goal is to achieve the best possible seizure control while minimizing side effects and optimizing the child’s overall well-being